Sustainability Policy : hastening the transition to a cleaner economy - Cohen, Steven, 1953 September 6-; Eimicke, William B.; Miller, Alison (Hoboken : Wiley, 2015)
A complete guide to sustainability policy at the federal, state, and local levels Sustainability Policy: Hastening the Transition to a Cleaner Economy is a fundamental guide for public sector professionals new to sustainability policy development, implementation, strategy, and practice. Featuring detailed cases highlighting innovative sustainability initiatives, this book explores the elements that constitute effective policy, and the factors that can help or hinder implementation and adoption. Readers gain insight into policies in effect at the federal, state, and local levels, in the areas o.
Why Are Cities Taking the Lead in Sustainability?
Includes bibliographical references (pages 227-261) and index.
Print version record.
Keywords: Since 2009; Sustainable development -- United States; United States -- Economic conditions -- 2009-; United States -- Economic policy -- 2009-; Sustainable development -- United States; LAW / Administrative Law & Regulatory Practice; Economic history; Economic policy; Sustainable development; United States -- Economic policy -- 2009-; United States -- Economic conditions -- 2009-; United States; Electronic books; Electronic books